Automation and fuzzy control of a manufacturing system - Hanane Zermane; Leila-Hayet Mouss; Sonia Benaicha (INTERNATIONAL JOURNAL OF FUZZY SYSTEMS and ADVANCED APPLICATIONS, 2021)
The automation of manufacturing systems is a major obligation to the developments because of exponential industrial equipment, and programming tools, so that growth needs and customer requirements. This automation is achieved in our work through the application programming tools from Siemens, which are PCS 7 (Process Control System) for industrial process control and FuzzyControl++ for fuzzy control. An industrial application is designed, developed and implemented in the cement factory in Ain-Touta (S.CIM.AT) located in the province of Batna, East of Algeria. Especially in the cement mill which gives the final product that is the cement.